Value of induced sputum analysis in asthma patients - Kania, Aleksander (2006)
Laboratory tests of induced sputum play an important role in non-invasive examination of the inflammatory process of the respiratory tract. Eicosanoids are a group of lipids, which reportedly play a significant role in the pathomechanism of asthma. The aim of the present thesis was to analyse the eicosanoids concentrations in induced sputum of patients suffering from bronchial asthma of pathogenetically different types: aspirin-induced asthma, aspirin- tolerant asthma (both atopic and nonatopic) and in healthy individuals. The study involved testing and analysis of induced sputum in 102 individuals, of whom 98 were qualified for sample analyses. The material obtained in the course of the study was analysed using state-of-the-art statistical methods, which permitted a precise tracking of the variables: eicosanoid levels (cys-LTs, 9α,11βPGF2, PGD2, PGF2α , PGE2), the proportion of cells in cytospin preparations of induced sputum as well as other variables. The study demonstrated that all asthma patients had elevated concentrations of cys-LTs in induced sputum in comparison with healthy subjects. The analysis of asthma patient groups showed that the levels of cys-LTs were highest in the aspirin-induced asthma. It was also found that the levels of 9α,11β-PGF2 in the supernatant of induced sputum in asthma patients were significantly higher than in healthy individuals. The analysis
Keywords: asthma; induced sputum; eicosanoids